Marna Pease (1866-1947): Founder of Biodynamics for the English-Speaking World - Paull, John; Harvey, Joan (Advances in Social Sciences Research Journal, 2023)
Marna Pease (1866-1947) was the founder of Biodynamic farming in Britain. The ‘Anthroposophical Agricultural Foundation’ (AAF) was inaugurated at the ‘World Conference on Spiritual Science and its Practical Applications’ (WCSS), London, July 1928, with Marna as the Honorary Secretary. Under the auspices of the AAF, Marna shepherded the fledgling Anglo Biodynamic (BD) movement through the turbulent times of the Great Depression (1929-1939), the Great Anthroposophy Purge (1935), and World War II (1939-1945). Marna stepped down in 1946. By that time there were reportedly over 400 members of the AAF. With Dr Carl Alexander Mirbt, she produced the first BD preparations in Britain at her home, Otterburn Tower, Northumberland. She took up the role of Honorary Secretary of both the AAF and the ‘Experimental Circle of Anthroposophical Farmers and Gardeners’. The AAF initially operated out of Otterburn (315 miles north of London, 74 miles south of Edinburgh). Marna was a member of the Executive Council of the Anthroposophical Society in Great Britain. She relocated to the Old Mill House at Bray-on-Thames (30 miles west of London) in 1930. Marna typed, bound, and despatched copies around the world, of the English translation of Rudolf Steiner’s ‘Agriculture Course’, to those who joined the Experimental Circle. She edited the first Biodynamics journal in English: ‘Anthroposophical Agricultural Foundation Notes and Correspondence’. Marna provided members with the BD preparations and she published BD pamphlets. She established a showcase Biodynamic garden and apiary at Bray-on-Thames. She recruited members, hosted visitors, and maintained an international correspondence with enquirers and members. Marna hosted Carl Mirbt (aka Mier) and his family, first at Otterburn and then at Bray. She hosted Dr Eugen Kolisko, Lilly Kolisko, and their daughter at Bray. Lilly’s ‘Biologisches Institut am Goetheanum’ (Biological Institute at the Goetheanum) relocated from Stuttgart to Bray in 1935. Marna was fluent in German and she translated Steiner’s ‘Nine Lectures on Bees’ (published 1933) and Lilly’s ‘The Moon and the Growth of Plants’ (published 1938). Marna’s legacy continues with the Biodynamic Agricultural Association (BDAA) in Britain, and with BD agriculture in the Anglo-sphere presently accounting for 30% of global BD agriculture.